Pengembangan LKPD IPA Berbasis Keterampilan Proses Sains untuk Meningkatkan Pemahaman Konsep Peserta Didik SMP - Yumni Amalina; Helmi Helmi; Pariabti Palloan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Twenty-first century science learning requires students to develop conceptual understanding through scientific activities, but learning processes are still often focused on memorization, causing students to experience difficulties in connecting concepts with real phenomena. This study aimed to develop science student worksheets based on science process skills that are valid, practical, and effective in improving junior high school students’ conceptual understanding. This research used a Research and Development (R&D) method with the 4D development model consisting of define, design, develop, and disseminate stages. The research subjects were seventh-grade students of SMP Negeri 4 Simboro. Data were collected using expert validation sheets, practitioner assessment questionnaires, and conceptual understanding tests through pretest and posttest activities. Data analysis was conducted using Aiken’s V index, practicality percentage analysis, and N-Gain. The results showed that the developed worksheet achieved a very valid category based on content, presentation, language, and graphical aspects and achieved a very practical category based on practitioner responses. The effectiveness of the worksheet was demonstrated by an improvement in students’ conceptual understanding with an N-Gain score of 73%, categorized as effective. These findings indicate that science process skills-based worksheets can facilitate students in conducting scientific activities and independently constructing concepts. This study concludes that the developed worksheet is appropriate to be used as science learning material to improve junior high school students’ conceptual understanding.